MANAJEMEN RISIKO PERUMAHAN SYARIAH TANPA KPR PERBANKAN: STUDI PADA NAKHIIL GARDEN PAWARENGAN - Muhammad Duta Kamal (2022)
In recent years, Indonesian government has actively developed sharia economic. One of the business sectors which is developed by sharia economic in Indonesia is sharia property sector. However, the development of sharia properties are still considered on high risk, especially for developers sharia property business whose not using any mortgages loan from bank. This study aims to examine risk management in sharia property business which are not used any banking mortgage and how to resolve these problems. This study used a descriptive qualitative method with a case study approach to sharia property business of Nakhiil Garden Pawarengan. The result of this study explains that in overcoming risks that arise in Nakhiil Garden, developers has carried out risk management which is considered to be able to minimize the impact of these risks. So that development of Nakhiil Garden properties can run smoothly.